mHealth Phone Intervention to Reduce Maternal Deaths and Morbidity in Cameroon: Protocol for Translational Adaptation - Budhwani H; Enah C; Bond CL; Halle-Ekane G; Wallace E; Turan JM; Szychowski JM; Long DM; Carlo WA; Tih PM; Tita AT (Dove Medical Press, 2022)
Henna Budhwani,1,2 Comfort Enah,3 Christyenne L Bond,1 Gregory Halle-Ekane,4 Eric Wallace,5 Janet M Turan,1,2,6 Jeff M Szychowski,7 Dustin M Long,7 Waldemar A Carlo,8 Pius M Tih,9 Alan TN Tita2,10 1Department of Health Policy and Organization, School of Public Health, University of Alabama at Birmingham, Birmingham, AL, USA; 2Center for Women's Reproductive Health, University of Alabama at Birmingham, Birmingham, AL, USA; 3School of Nursing, College of Health Sciences, University of Massachusetts Lowell, Lowell, MA, USA; 4Department of Obstetrics and Gynaecology, University of Buea, Buea, Cameroon; 5Depatrment of Medicine, School of Medicine, University of Alabama at Birmingham, Birmingham, AL, USA; 6School of Medicine, Koç University, Istanbul, Turkey; 7Department of Biostatistics, School of Public Health, University of Alabama at Birmingham, Birmingham, AL, USA; 8Depatrment of Pediatrics, School of Medicine, University of Alabama at Birmingham, Birmingham, AL, USA; 9Cameroon Baptist Convention Health Services, Bamenda, North West Region, Cameroon; 10Depatrment of Obstetrics and Gynecology, School of Medicine, University of Alabama at Birmingham, Birmingham, AL, USACorrespondence: Henna Budhwani, Department of Health Policy and Organization, School of Public Health, University of Alabama at Birmingham, 330C Ryals Public Health Building, 1720 University Boulevard, Birmingham, AL, 35294, USA, Tel +1 205 975 7613, Fax +1 205 975 7685, Email budhwani@uab.eduPurpose: The purpose of this NIH-funded protocol is to adapt (Aim 1) and pilot test (Aim 2) an mHealth intervention to improve maternal and child health in Cameroon. We will adapt the 24/7 University of Alabama at Birmingham Medical Information Service via Telephone (MIST) provider support system to mMIST (mobile MIST) for peripheral providers who provide healthcare to pregnant and postpartum women and newborns in Cameroon.Methods: In Aim 1, we apply qualitative and participatory methods (in-depth interviews and focus groups with key stakeholders) to inform the adaptation of mMIST for use in Cameroon. We use the sequential phases of the ADAPT-ITT framework to iteratively adapt mMIST incorporating qualitative findings and tailoring for local contexts. In Aim 2, we test the adapted intervention for feasibility and acceptability in Ndop, Cameroon.Results: This study is ongoing at the time that this protocol is published.Conclusion: The adaptation, refinement, and pilot testing of mMIST will be used to inform a larger-scale stepped wedged cluster randomized controlled effectiveness trial. If successful, this mHealth intervention could be a powerful tool enabling providers in low-resource settings to deliver improved pregnancy care, thereby reducing maternal and fetal deaths.Keywords: pregnancy, mobile applications, mHealth, intervention, maternal health